A THEORETICAL AND METHODOLOGICAL APPROACH TO TRANSFORMATION OF THE ACCOUNTING SYSTEM IN THE HOTEL BUSINESS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This thesis develops a methodological approach to transforming the accounting system, which provides for determining financial results in the hotel industry by service segments, assessing the profitability of revenue centers, and integrating these indicators into management decisions. As a scientific innovation, an integrated model is proposed that allows for the separation of income and expenses for hotel services by specific segments and the reflection of their profitability level in management reports in real time. The proposed approach serves to bring the process of making financial management decisions of hotel entities to a qualitatively new level.